2007
DOI: 10.1142/s0217732307024127
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Klein–gordon Equation in a Generalized Kaluza–klein Monopole Background

Abstract: We investigate solutions of the Klein-Gordon equation in a class of five dimensional geometries presenting the same symmetries and asymptotic structure as the Gross-Perry-Sorkin monopole solution. Apart from globally regular metrics, we consider also squashed Kaluza-Klein black holes backgrounds.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The topology of the horizon of SqKK black holes is S 3 , while it looks like four dimensional black holes with a circle as an internal space in the asymptotic region. SqKK black holes were originally derived as five-dimensional vacuum solutions in the context of Kaluza-Klein theory [11,12].Recently, much effort has been devoted to reveal the properties of squashed Kaluza-Klein black holes [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Since the horizons of these black holes have the same nature as the fivedimensional black holes, Hawking radiation and quasi-normal modes from SqKK black holes would be different from those seen in four-dimensional black holes even at low energy [22,27,28].…”
mentioning
confidence: 99%
“…The topology of the horizon of SqKK black holes is S 3 , while it looks like four dimensional black holes with a circle as an internal space in the asymptotic region. SqKK black holes were originally derived as five-dimensional vacuum solutions in the context of Kaluza-Klein theory [11,12].Recently, much effort has been devoted to reveal the properties of squashed Kaluza-Klein black holes [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Since the horizons of these black holes have the same nature as the fivedimensional black holes, Hawking radiation and quasi-normal modes from SqKK black holes would be different from those seen in four-dimensional black holes even at low energy [22,27,28].…”
mentioning
confidence: 99%
“…The MP spacetimes are members of more general classes, including: (i) the Israel-Wilson class [62]; (ii) higher-dimensional MP spacetimes [35]; (iii) the Kastor-Traschen class [63]. In each of these cases, the black holes are extremally charged.…”
Section: Other Spacetimesmentioning
confidence: 99%
“…Contopoulos revealed that the binary MP spacetime exhibits selfsimilarity and chaotic dynamics [16][17][18][19][20][21][22]. Influential perspectives on the role of chaos in binary systems in relativity have followed from Yurtsever [23], Dettmann [24,25], Cornish [26,27], Frankel [28], Levin [29,30] and many others [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Several aspects of SqKK black holes are also discussed, e.g. thermodynamics [48][49][50], Hawking radiation [51][52][53], gravitational collapse [54], behavior of the Klein-Gordon equation [55], stability for the neutral case [56] 1 , quasinormal modes [57,58], geodetic precession [59], Kerr/CFT correspondence [60] and gravitational lensing effects [61].…”
Section: Introductionmentioning
confidence: 99%